Fundamental investigations of hydrocarbon plasma chemistry: mechanistic studies of gas-phase processes and plasma-surface interactions - Van Surksum, Tara, author; Fisher, Ellen R., advisor; Van Orden, Alan K., committee member; Ravishankara, A. R., committee member; Weinberger, Christopher R., committee member (Colorado State University. Libraries, 2020)
To view the abstract, please see the full text of the document.